Valorization of waste: innovative techniques for extracting bioactive compounds from fruit and vegetable peels - a comprehensive review - Khan, Rahim; Anwar, Farooq; Mohamad Ghazali, Farinazleen; Mahyudin, Nor Ainy (Elsevier, 2024)
Fruits and vegetables are valuable commodities in horticultural production due to their bioactive components, which promote health. However, processing these products results in a significant waste, with discarded peels, accounting for 90–92 % of the total waste. These waste materials contain high levels of bioactives that can be extracted to enhance their value by utilizing them as valuable ingredients in food and pharmaceutical products. This review compares and explores the potential of conventional and non-conventional extraction methods, including microwave-assisted (MA), ultrasound-assisted (UA), pulsed electric fields (PEP), pulsed electric heating (PEH), pressurized liquid extraction (PLE), supercritical fluid extraction (SFE), pressurized hot water (PHW), high hydrostatic pressure (HHP), and enzyme-assisted extraction (EAE) for the extraction of bioactive compounds from fruit and vegetable peels. The focus of this study was to achieve higher extraction yields through the applications of non-conventional technologies. Moreover, this review highlights the use of efficient, innovative technologies to maximize the value-added potential of fruit and vegetable wastes while ensuring environmental preservation and supporting a circular economy. The review findings are expected to be valuable resources for the fruit and vegetable processing industry, providing insights into the potential application of economical and efficient sustainable extraction methods.